2020
DOI: 10.1016/j.dib.2020.106083
|View full text |Cite
|
Sign up to set email alerts
|

Dataset on determinants of intention and investment behaviour amongst young Indonesian millennials

Abstract: The dataset examines three factors (i.e. financial literacy, self-control, peer-influence) that influence investment behaviour amongst young Indonesian millennials. Using a non-probability sampling technique, a total of 265 young millennials attending Investment Gallery seminar and workshop events in Jakarta, Indonesia completed an investment behaviour survey. The reflective measurement was performed using the Partial Least Square Structural Equation Model (PLS-SEM) to the screened data from the survey ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 1 publication
0
4
0
1
Order By: Relevance
“…The collected data were analyzed using Partial Least Square Structural Equation Modeling (PLS-SEM to gain the best measurement [2 , 3] and the model is presented in Fig. 1 .…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The collected data were analyzed using Partial Least Square Structural Equation Modeling (PLS-SEM to gain the best measurement [2 , 3] and the model is presented in Fig. 1 .…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…The collected data were tabulated using an excel application and filtered for missing values and outliers before the analysis. Literature [3 , 4] has suggested that the number of outliers (residual value higher than 1.96) will be deleted from the data. The removal of outlier data was expected to improve the PLS-SEM results [5] .…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…sikap dapat dipandang sebagai penentu yang mendasari minat individu untuk berinvestasi. Berbagai penelitian menunjukkan bahwa sikap memiliki dampak positif dan signifikan terhadap minat berinvestasi penelitian dari (Azizah & Mulyono, 2020;Hapsari, 2021;Alleyne & Broom, 2011;Cuong, P. K., & Jian, 2014;Ramasubbian et al, 2018;Raut et al, 2018;Salisa, 2021;Yoopetch & Chaithanapat, 2021) membuktikan secara empiris bahwa sikap memiliki dampak yang signifikan terhadap minat investor untuk berinvestasi. Akan tetapi peneliti menemukan beberapa penelitian (Seni & Ratnadi, 2017;Setyorini & Indriasari, 2020) yang memiliki inkonsisten dengan hasil penelitian terkait yang dinyatakan tidak berpengaruh secara signifikan terhadap minat investasi.…”
Section: Pendahuluanunclassified
“…As such, they operationalize an implicit or explicit definition of FL. For example, Ram et al (2020) and Azizah et al (2020) analyzed FK to direct remedial actions and promote public policy [58,59]. Researchers analyzed financial market consumption behavior [60], and other studies focus on FL and the effect of FE in a specific subgroup in society [61].…”
Section: Fl Scales In the Literaturementioning
confidence: 99%